Developing Transferable Research Skills in First Year Agricultural Economics Students - Koppi, Tony; Nolan, Elizabeth; Field, Damien (Journal of University Teaching and Learning Practice, 2010)
A problem-based learning approach was adopted for a unit of study in first year agricultural economics at the University of Sydney with the aim of starting development of students’ research skills earlier than usual. The novel teaching approach employed a structured and guided problem activity in the first semester and progressed to a more authentic problem activity in the second semester where the students worked in online peer groups to identify their own problem within a specified challenging area (market failure), carry out research and discuss findings prior to submitting an individual essay on their chosen topic. A structured learning journal with 10 questions was used in the second semester where the students recorded their reflections on a range of aspects of the learning process. None of the questions specifically asked about research yet 72% of the students mentioned it at least once. These learning journals were analysed for unsolicited comments about learning and research to gauge what the students themselves believed they had learned about research and how it can be transferred to other disciplines and future employment. The final essays were independently analysed by using eight research performance criteria to estimate the degree of research skills displayed by the students. Most of the students performed well in six of the research criteria indicating that development of research skills can be initiated in the first year of a degree program.